2018
DOI: 10.2355/isijinternational.isijint-2018-236
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hydrogen Distribution in Pure Iron Using WO<sub>3</sub> Thin Film

Abstract: The usefulness of a new approach to detecting the distribution of hydrogen absorbed into pure iron utilizing a WO 3 thin film was demonstrated in this study. A WO 3 film with an electrochromic property was formed on the hydrogen detection side of iron sheet by reactive magnetron sputtering. After hydrogen was absorbed into the iron sheet by cathodic polarization on the hydrogen absorption side, the color of the WO 3 film corresponding to the electrode area changed from light blue to dark blue. The WO 3 film wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…Figure 2(d) exhibited the color change from light blue to dark blue occurred only around the part corresponding to the hydrogen charging area. Our previous research showed that the color change is caused by the formation of H x WO 3 , 26) and this result indicates the local hydrogen uptake into the specimen could be visualized by the phase transition of WO 3 .…”
Section: Hydrogen Detection For the Specimen With Pdmentioning
confidence: 83%
See 2 more Smart Citations
“…Figure 2(d) exhibited the color change from light blue to dark blue occurred only around the part corresponding to the hydrogen charging area. Our previous research showed that the color change is caused by the formation of H x WO 3 , 26) and this result indicates the local hydrogen uptake into the specimen could be visualized by the phase transition of WO 3 .…”
Section: Hydrogen Detection For the Specimen With Pdmentioning
confidence: 83%
“…25) We reported an approach to detecting the distribution of hydrogen uptake into pure iron using a WO 3 thin film. 26) WO 3 has the electrochromic property, and its optical property changed by the formation of H x WO 3 . 27,28) In our approach, Pd was electrochemically-coated, and the WO 3 film was subsequently formed on the hydrogen detection side of the pure iron sheet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…自動車の衝突安全性の向上や車両重量の軽量化による省 エネルギー化を目的として,自動車用鋼板は近年高強度化 されており,引張強度 980 MPa を超える高強度鋼板が実用 化されている。しかし,鉄鋼材料は引張強度が 980 MPa を 超えると水素脆化の発現が問題となる 1,2) 。これまで自動車 用鋼板の水素脆化特性は,通常ひずみ速度引張試験 [3][4][5][6]) や, 低ひずみ速度引張試験 7-9) ,定荷重試験 10,11) などで評価され てきた。しかし,自動車用高強度鋼板の多くは各種部品形 状にプレス成形して使用されるので,プレス成形にともな い残留応力や塑性ひずみが導入される 12) 。さらに,残留応 力勾配や塑性ひずみによって鋼内部での水素拡散は促進ま たは抑制され,その結果水素の局在化が起こる。したがっ て,プレス成形が施された高強度鋼板の水素脆化特性は, 残留応力や塑性ひずみ,水素拡散挙動や局所水素量の影響 を考慮して評価する必要がある。 プレス成形鋼板の水素脆化特性については Toji らが U 曲 げ試験片を用いて,塑性ひずみ,負荷応力と侵入水素量が 水素脆化特性へ与える影響を検討している 13) 。その結果, 負荷応力が高く,塑性ひずみが大きく,侵入水素量が多い 条件で割れが発生すると報告している。また,著者らはこ れまでに,U 曲げ加工 14,15) や張出し加工 12,16) 17) はこれまでに水素マイ クロプリント法 [18][19][20] ,銀デコレーション法 [21][22][23][24][25] ,二次イオ ン質量分析法 [26][27][28][29] や表面電位測定 [30][31][32][33][34] を用いる方法などの いくつかの方法が提案されている。これらの方法は高解像 度で鋼材中の水素分布を得ることができる。中でも表面電 位測定を用いるケルビンプローブフォース顕微鏡は,高い 空間分解能に加えて時間分解能を持つことが報告されてい る [30][31][32][33] 。これらの方法は高空間分解能を生かして主に金属 の微細組織に着目したミクロな水素分布の検出に用いられ ている。一方,サブミリ以上のマクロな水素分布を観察す る方法は,表面電位を用いる走査型ケルビンプローブ 34) や 金属酸化膜 35)…”
Section: 緒言unclassified
“…To date, some techniques have been reported to analyze the distribution of hydrogen in metals. [14][15][16][17][18][19][20][21] Silver decoration and hydrogen microprint techniques are the most representative methods to visualize the local distribution of hydrogen in metals. [17,18] However, the techniques require the ex situ observation by a secondary electron microscope, in other words, they cannot capture the time variations of the hydrogen distribution.…”
mentioning
confidence: 99%